Socioeconomic and indigeneity determinants of the consumption of non-timber forest products in Vietnam's Bu Gia Map National Park. Issue 7 (3rd October 2019) - Nguyen, T.; Lawler, S.; Paul, W.
ABSTRACT: Conservation of protected areas requires understanding of the consumption of forest products by rural people who live near protected forests. Socioeconomic factors such as a better education, income, land holding size, have been used to understand the patterns of consumption of non-timber forest products (NTFPs). Ethnicity, and especially whether or not people are indigenous to the forested areas, may also change consumption patterns. In this study we analysed the socioeconomic factors, indigeneity and geographical locations of people living in the buffer zones of Vietnam's Bu Gia Map National Park to better understand the key determinants of the consumption of NTFPs. We conducted 121 interviews with local households and found that indigeneity, education, family size, and the area of land used were statistically significant in explaining the amount of NTFPs consumed, while indigeneity and area of land used by local people had positive relationships with the diversity (measured in number of categories) of NTFPs consumed by local people. Interestingly, there were statistically significant effects of interactions between the area of land used and indigeneity on the consumption of NTFPs. The amount of these products is important for indigenous people who belong to the groups using small and medium areas of land. The medium land use group consumed significantly fewer categories of NTFPs than the small and large land use groups. This data may help local managers to develop interventions that support biodiversity conservation, promote sustainability of these important resources and improve the social welfare of marginal groups.